Pengaruh Kompetensi dan Profesionalisme Terhadap Kinerja Pegawai Dengan Komitmen Organisasi Sebagai Variabel Intervening - Fauzia Ratna Dewi; Nunik Kusnilawati; Albert (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
As a supervisory body in the execution of regional administration in Grobogan Regency, the Grobogan Regency Inspectorate is crucial to achieving successful governance. Based on observations, it appears that employees of the Grobogan Regency Inspectorate tend to perform below par, as shown by the fact that the Follow-up to the Inspection Results (TLHP) completed by the Grobogan Regency Inspectorate has not been completed at the best rate for five years in a row. The purpose of this study is to ascertain how the performance of Grobogan Regency Inspectorate workers relates to their professionalism, competence, and organizational commitment. Using a total enumeration (census) technique, this study was carried out in the Grobogan Regency Inspectorate setting with the full involvement of all 49 members of the community. The methodology of this study is based on a quantitative approach, in which respondents are given questionnaires to complete in order to gather data. Additionally, the Partial Least Square (PLS) method was employed as the statistical analytic tool for data processing and analysis. Data processing findings demonstrate that professionalism and competency greatly boost organizational commitment. Furthermore, employee performance is positively impacted by the three factors of competence, professionalism, and organizational commitment. Organizational commitment, however, was only able to moderate the impact of professionalism on performance; it was unable to mediate the relationship between employee performance and competence. ‎